2021
DOI: 10.1002/app.51889
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite/cellulose derivatives‐based bionanocomposites for controlled naproxen delivery

Abstract: Bionanocomposites are biocompatible, biodegradable, low‐toxicity materials inorganic/biopolymer‐based, carrying drugs for controlled delivery. The development of novel materials aiming to improve drug efficacy and reduce its toxicity is a continuous focus of the pharmaceutical industry. In this work, we report the development of an innovative controlled naproxen delivery system. The bionanocomposites are composed of naproxen‐loaded halloysite and ethylcellulose/hydroxypropylmethylcellulose blends produced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“… SEM images of ( a ) naproxen; ( b ) unloaded HNT (10 kx); ( c ) unloaded HNT (50 kx); ( d ) naproxen-loaded HNT; ( e ) nanocomposite (HNT:EC:HPMC 1:1:2); ( f ) nanocomposite (HNT:EC:HPMC 1:2:1). Reproduced with permission from [ 53 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… SEM images of ( a ) naproxen; ( b ) unloaded HNT (10 kx); ( c ) unloaded HNT (50 kx); ( d ) naproxen-loaded HNT; ( e ) nanocomposite (HNT:EC:HPMC 1:1:2); ( f ) nanocomposite (HNT:EC:HPMC 1:2:1). Reproduced with permission from [ 53 ]. …”
Section: Figurementioning
confidence: 99%
“…Permeability studies revealed that isoniazid transport across Caco-2 cellular membranes was improved, and the nanocomposite was efficiently internalized by the cells [52]. Similarly, naproxen-loaded HNT and ethylcellulose/hydroxypropylmethylcellulose blends were processed by spray drying (Figure 7), and a nanocomposite was obtained by ionic interaction [53]. HNTs have also been proposed for other applications, such as cancer, vaginal, and to enhance blood-brain barrier permeation.…”
Section: Drug Delivery Applicationsmentioning
confidence: 99%